Biskuit “Fishbean” sebagai Alternatif MP-ASI Lokal Tinggi Protein dan Vitamin A - Emy Yuliantini; Kamsiah Kamsiah; Meriwati Meriwati (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
Less energy protein (PEM) and vitamin A deficiency have a close relationship. PEM in children can lead to a deficiency of vitamin A because it can lead to inhibition of absorption, transport, and the conversion of vitamin A. One of the local food sources of protein that can be used as a complementary feeding biscuits are catfish and red beans (Pangasius spp). This study aims to analyze the contribution of complementary feeding baby biscuit with substitution catfish and red beans on the adequacy of protein and vitamin A in infants. This research is purely experimental and quasi using a randomized block design (RBD) were performed with a preliminary study fishebean biscuit formulation development and the value of the nutrient content in the laboratory of Food Technology Ministry of Health polytechnic Bengkulu. The population is infants and toddlers in PHC Banyan Kingdom as the case group and control group Lempuing health centers. Total sample of 30 people, the sampling method Non-Probability Sampling. Data were collected by questionnaire respondents, organoleptic test form, and food recall intake for 3 days. Data were analyzed by one-way ANOVA and the average difference test by the independent method sample t-test. The result showed no difference in the intake of protein and vitamin A in the treatment group (fed babies biscuit fishbean) and control groups (infants fed biscuit pabrikkan) . There are differences in the intake of protein and vitamin A between the control group with the cases at an average contribution of the adequacy of protein biscuit fishbean baby was 19.60 grams .